Excessive fluoride consumption increases haematological alteration in subjects with iron deficiency, thalassaemia, and glucose-6-phosphate dehydrogenase (G-6-PD) deficiency - Pornprasert S. (2017)
© 2016, Springer Science+Business Media Dordrecht. Excessive fluoride consumption leads to accelerated red blood cell death and anaemia. Whether that increases the haematological alteration in subjects with haematological disorders (iron deficiency, thalassaemia, and G-6-PD deficiency) is still unclear. The fluoride in serum and urine and haematological parameters of students at Mae Tuen School (fluoride endemic area) were analysed and compared to those of students at Baan Yang Poa and Baan Mai Schools (control areas). Iron deficiency, thalassaemia, and G-6-PD deficiency were also diagnosed in these students. The students at Mae Tuen School had significantly (P  <  0.001) higher levels of mean fluoride in the serum and urine than those in control areas. In both control and fluoride endemic areas, students with haematological disorders had significantly lower levels of Hb, Hct, MCV, MCH, and MCHC than those without haematological disorders. Moreover, the lowest levels of Hb, MCH, and MCHC were observed in the students with haematological disorders who live in the fluoride endemic area. Thus, the excessive fluoride consumption increased haematological alteration in subjects with iron deficiency, thalassaemia, and G-6-PD deficiency and that may increase the risk of anaemia in these subjects.